Instrumentation for engineering measurements - Dally, James W.; Riley, William F.; McConnell, Kenneth G. (New York : Wiley, 1993)
The primary objective of thisbook is to introduce electronic instrumentation systems in a manner sufficiently complete that the reader will acquire an ability to make accurate and meaningful measurements of mechanical and thermal quantities.
Applications of electronic instrument systems -- Analysis of circuits -- Analog recording instruments -- Digital recording systems -- Sensors for transducers -- Signal conditioning circuits -- Resistance-type strain gages -- Force, torque, and pressure measurements -- Displacemetn, velocity, and Acceleration measurements -- Analysis of vibrating systems -- Temperature measuremetns -- Fluid flow measuremetns -- Statistical methods --
Includes index.
Keywords: ENGINEERING INSTRUMENTS